Proses Pengujian Kebocoran Valve Pada Km. Kendhaga Nusantara Menggunakan Hydrostatic Pressure Test - Adi Kurniawan Yusim; Muhammad Afif Fadila; Sarwoko Sarwoko (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
The process of testing the leak on the valve on the important stages of vessels is carried out and regulated by the BiroKlasifikasi Indonesian (BKI) as a Class which refers to the International Association of Classification Societies (IACS).Pipes and fittings shall be tested by hydrostatic pressure not less than 1.5 times the nominal pressure. In this study, the 4gate valves tested had a nominal pressure from the manufacturer of 10 bar, so they had to be tested up to a pressure of 15bar. The valves have been tested one by one with the Hydrostatic Pressure Test method, using the Test Pump. From the test results found a leak in one of the valves, namely in the disc. The ecommendation given by BKI is to repair it by covering the leak using the material recommended rom the gate valve manufacturer using epoxy type iron glue.